Long-Range Optomechanical Interactions in SiN Membrane Arrays - Xiong Yao; Matthijs H. J. de Jong; Jie Li; Simon Gröblacher (Physical Review X)
Optomechanical systems using a membrane-in-the-middle configuration can exhibit a long-range type of interaction similar to how atoms show collective motion in an optical potential. Photons bounce back and forth inside a high-finesse Fabry-Pérot cavity and mediate the interaction between multiple membranes over a significant distance compared to the wavelength. Recently, it has been demonstrated that off-resonant coupling between light and the intermembrane cavity can lead to coherent mechanical noise cancellation. On-resonance coupling of light with both the Fabry-Pérot and intermembrane cavities, predicted to enhance the single-photon optomechanical coupling, have to date not been experimentally demonstrated, however. In our experiment, a double-membrane system inside a Fabry-Pérot cavity resonantly enhances the cavity field, resulting in a stronger optomechanical coupling strength from the increased radiation pressure. The resonance condition is first identified by analyzing the slope of the dispersion relation. Then, the optomechanical coupling is determined at various chip positions over one wavelength range. The optimum coupling conditions are obtained and enhancement is demonstrated for double-membrane arrays with three different reflectivites, reaching nearly fourfold enhancement for the collective motion of R=65% double membranes. The cavity losses at the optimum coupling are also characterized and the potential of reaching the single-photon strong coupling regime is discussed.